2005
DOI: 10.2223/jped.1394
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus and acute bronchiolitis in young infants

Abstract: Rhinovirus was the second most common agent detected in nasal secretions from young infants hospitalized with acute bronchiolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…After Papadopoulos et al 22 demonstrated that rhinovirus can directly infect the lower airway (i.e., it is not limited to the upper airway as once thought), many epidemiologic studies have shown that rhinovirus is an important causative pathogen of lower respiratory infection in children. [4][5][6][7][8][9][10][11][12][13][14][15] This virus can indeed cause all sorts of lower respiratory illnesses; such as bronchiolitis, pneumonia and asthma exacerbation. 23 As assessed by molecular methods, the prevalence of rhinovirus causing acute lower respiratory infection among young children <3 years of age varies between 17 and 35%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After Papadopoulos et al 22 demonstrated that rhinovirus can directly infect the lower airway (i.e., it is not limited to the upper airway as once thought), many epidemiologic studies have shown that rhinovirus is an important causative pathogen of lower respiratory infection in children. [4][5][6][7][8][9][10][11][12][13][14][15] This virus can indeed cause all sorts of lower respiratory illnesses; such as bronchiolitis, pneumonia and asthma exacerbation. 23 As assessed by molecular methods, the prevalence of rhinovirus causing acute lower respiratory infection among young children <3 years of age varies between 17 and 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathogens-such as human metapneumovirus (hMPV), influenza virus, parainfluenza virus, adenovirus as well as Mycoplasma pneumoniae-also cause wheezing in children. [2][3][4][5] Recently, rhinovirus was reported as frequently as RSV among children hospitalized with wheezing illnesses [6][7][8][9][10][11] and a number of studies have shown that it is a significant risk factor for subsequent wheezing and/or development of asthma. [12][13][14][15][16] Epidemiologic studies on the prevalence of the causative pathogens in young children suffering from an acute wheezing episode and their impact on subsequent respiratory illnesses in Thailand are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Infants and toddlers younger than three years of age, with a diagnosis of LRTI, admitted to the emergency room (ER) or pediatric wards of a tertiary hospital in Porto Alegre, southern Brazil, were recruited for this study, during the months of greatest prevalence for acute pediatric respiratory viral illnesses (i.e., from April to November) in 2007 [4,15]. The great majority of patients seen in this particular setting come from low-income families, with health coverage provided by the Brazilian free-access public health system.…”
Section: Subjects and Study Designmentioning
confidence: 99%
“…Although RSV is well recognized as the main agent associated with severe LRTIs, recent data indicate that other viruses may play a significant role in these clinical outcomes. Human rhinovirus (HRV) seems to be of particular interest, as the most prevalent virus in respiratory illnesses even in the first years of life [4,5], being associated with severe acute bronchiolitis, especially among children of atopic parents [6]. Moreover, a recent study showed that, in a population of preterm infants, HRV was the most prevalent agent associated with severe bronchiolitis [7].…”
Section: Introductionmentioning
confidence: 99%
“…15 The impact of these and other newly discovered viruses in the epidemiology of CAP in developing countries is yet to be completely elucidated but recent data suggest it is unlikely that the distribution is much different from that found in developed countries. 16,17 Other viruses like influenza B, parainfluenza 1 and 2, and cytomegalovirus are often implicated in the etiology of CAP in children and have to be accounted for. 1,4,18 Streptococcus pneumoniae is the main bacterium causing pneumonia in children under the age of 5.…”
Section: Etiologymentioning
confidence: 99%